2020
DOI: 10.1097/jnr.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Active Music Therapy Program on Functional Fitness in Community Older Adults

Abstract: Background Health problems common among older adults living in community settings include a lack of functional fitness. Many studies have confirmed that exercises and static music therapy improve physical and psychological health problems. Exercise programs involving music have a higher frequency of attendance and motivation than other exercise programs. Active participation in active group music therapy results in better therapeutic effects. Purpose Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A reasonable number of studies presented results related to the elderly population, with emphasis on the use of membranophones in a long-stay institution, as they require less cognitive demand, providing an improvement in mood and in quality of life, ability to imitate rhythm patterns that gradually become more complex ( 18 ) . These findings are validated by other studies showing positive results in the elderly population after music therapy interventions ( 38 , 42 , 43 , 44 , 45 ) . Another finding, inherent to the elderly population is related to the vibrating responses (when the drum was placed on the participant’s lap and the participant felt the vibration), which lasted longer than the non-vibrating responses (when the drum was held by a music therapist, in front of the participant, off the patient’s lap) ( 19 ) .…”
Section: Discussionsupporting
confidence: 87%
“…A reasonable number of studies presented results related to the elderly population, with emphasis on the use of membranophones in a long-stay institution, as they require less cognitive demand, providing an improvement in mood and in quality of life, ability to imitate rhythm patterns that gradually become more complex ( 18 ) . These findings are validated by other studies showing positive results in the elderly population after music therapy interventions ( 38 , 42 , 43 , 44 , 45 ) . Another finding, inherent to the elderly population is related to the vibrating responses (when the drum was placed on the participant’s lap and the participant felt the vibration), which lasted longer than the non-vibrating responses (when the drum was held by a music therapist, in front of the participant, off the patient’s lap) ( 19 ) .…”
Section: Discussionsupporting
confidence: 87%
“…• This paper highlights that after a 3-month musical fitness programme intervention, neuropsychiatric symptoms and depression decreased in older adults with cognitive impairment in long-term care facilities. physical interventions may enhance improvements in the health and functional independence of older adults with cognitive impairment (Chan & Chen, 2020;Langhammer et al, 2019). A combination of music therapy and physical activity is a non-invasive and safe intervention; nevertheless, its effects on neuropsychiatric symptoms, depression, upper-limb muscle strength and cognitive functions among institutionalised older adults are uncertain since limited evidence-based studies have been conducted.…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…As mentioned above, it seems that the combination of these two types of interventions can target both physical and cognitive deficits, thereby maximising the efficacy of intervention efforts and beyond the effects of a single‐component intervention (Fessel et al, 2017). There is emerging evidence that integrated music and physical interventions may enhance improvements in the health and functional independence of older adults with cognitive impairment (Chan & Chen, 2020; Langhammer et al, 2019). A combination of music therapy and physical activity is a non‐invasive and safe intervention; nevertheless, its effects on neuropsychiatric symptoms, depression, upper‐limb muscle strength and cognitive functions among institutionalised older adults are uncertain since limited evidence‐based studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, MST increased the activity and connectivity between the auditory and motor cortical regions by providing individuals with auditory feedback for errors and real-time movement adjustments, which consequently boosted motor recovery of the upper limbs of stroke patients [18]. In addition to patients with neurological de cits, a recent study also revealed that active music therapy has effects on improving upper limb muscle power in community dwelling older adults [19]. However, the effects of MST on the sensorimotor control capacity of an aging hand closely related to lifestyle and living quality are as yet not well known.…”
Section: Introductionmentioning
confidence: 99%